DAMPAK TATA KELOLA PEDAGANG KAKI LIMA (PKL) TERHADAP KINERJA USAHA (STUDI PADA PKL WILAYAHSEKITAR KAMPUS DI KOTA JAMBI) - Erwita Dewi; Raja Sarah Fatricia (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
The goal of this research is to identify factors that influence the street vendor’s governance (PKL) around some universities in Jambi city. It also intended to explain the impact of PKL governance on business performance by quantitative model. The data analysis is divided into two, namely descriptive and inferential statistics. The inferential statistics employs Partial Least Square (PLS).The samples are taken based on purposive sampling method;a judgement method with 7,5% assumption on street vendors around universities in Jambi city. The result indicates that human resource and operational management have effect on business performance, while finance and marketing have no effect on business performance. Hence, governance model on the future should be considered human resource as the primary asset of PKL.